Hepatoprotective effect of fermented soybean (nutrient enriched soybean tempeh) against alcohol-induced liver damage in mice - Mohd Yusof, Hamidah; Mohd Ali, Norlaily; Yeap, Swee Keong; Ho, Wan Yong; Beh, Boon Kee; Koh, Soo Peng; Long, Kamariah; Abdul Aziz, Suraini; Mohammed Alitheen, Noorjahan Banu (Hindawi Publishing Corporation, 2013)
Recently, soybean tempeh has received great attention due to many advantages such as higher nutritional value, lower production cost, and shorter fermentation time. In this study, the in vivo hepatoprotective and antioxidant effects of nutrient enriched soybean tempeh (NESTE) were determined. NESTE fermentation process which involved anaerobic incubation was previously proclaimed to increase the content of amino acids and antioxidant properties remarkably. The evaluation of histological sections, serum biochemical markers (aspartate aminotransferase (AST), alanine aminotransferase (ALT), and cholesterol and triglycerides (TG)), liver immune response level (nitric oxide (NO)) and liver antioxidant level (superoxide dismutase (SOD), ferric reducing antioxidant power (FRAP), and malondialdehyde (MDA)) was conducted in order to compare the effects of nonfermented soybean extract (SBE) and fermented soybean extract (NESTE) on alcohol-induced liver damage in mice. Results demonstrated that 1000 mg/kg of NESTE can significantly reduce the levels of AST, ALT, cholesterol, TG, MDA, and NO. On the other hand, it also raised the level of SOD and FRAP. Furthermore, the histological examination on 1000 mg/kg NESTE treatment group showed that this extract was capable of recovering the damaged hepatocytes to their normal structures. Thus, it can be concluded that NESTE produced through fermentation process was able to enhance hepatoprotective and antioxidant effects in vivo.